First record of mass wild waterfowl mortality due to Clostridium botulinum in Brazilian semiarid - Lima, Pedro C. (2020)
In 2008, 270 wild birds from aquatic environments were found dead or debilitated on the banks of smaller lakes that had been formed due to the decrease in the level of the holding lake of the Sobradinho Dam located on the Sao Francisco River in the Caatinga of Bahia, Brazil. The outbreak occurred months after the dam's partial drainage, with the formation of puddles that accumulated decomposing organic material. Amongst the 270 individuals examined and/or found dead, the majority (50%) of the birds found belonged to the Anatidae family. The debilitated birds presented neurological clinical signs including lack of motor coordination, weakness, grave flaccid paralysis in the legs, wings, neck and eyelids, diarrhea, and dyspnea. Tissue samples of the birds were collected, as were water samples and samples of the substrate of the lakes. Zoonotic arboviroses or heavy metals were not detected. Analyses of liver and digestive tract content samples through bioassay and serum neutralization in mice revealed the presence of type C botulinic toxin in the viscerae samples, and type D in sediment samples. According to our knowledge, this is the first record of an outbreak of botulism in wild birds in natural conditions in Brazil.